Literature Study On The Effect Of On The Job Training On Work Readiness - Bambang Junipitoyo; I Wayan Susila; Any Sutiadiningsih (International Journal of Science, Technology & Management, 2021)
Experience on the job training will help students improve the competence of graduates to align with what is needed. In addition to developing competencies, learning through experience on the job training will stimulate the development of character and also a work ethic of discipline, responsibility, honesty, cooperation, leadership, and others according to what is needed by the industry. The creation of competence, character and work ethic is expected that graduates will be ready to welcome the competition of the ASEAN Economic Community (AEC). This research was conducted based on a literature study of various theoretical studies regarding experiences on the job training. Where these studies are an initial description in conducting research, especially those related to the influence of experiences on the job training. Based on the results of data analysis with several similar research literature, the effect of on the job training experience on graduate work readiness is very significant and it can be concluded that there is a significant effect on the job training experience on graduate work readiness.